Clinical concentrations of morphine are cytotoxic on proliferating human fibroblasts in vitro. Issue 11 (November 2016) - Aguirre, José; Borgeat, Alain; Hasler, Melanie; Bühler, Philipp; Bonvini, John M.
Abstract : BACKGROUND: Morphine and other opioids are routinely used systemically and as wound infusions in the postoperative period. Their effect on wound and fracture healing remains unclear. OBJECTIVE: The primary outcome was to assess the potential cytotoxicity of clinically relevant concentrations of morphine on human fibroblasts. DESIGN: Laboratory in-vitro study. SETTING: Institute of Physiology, Zurich Center for Integrative Human Physiology, University of Zurich. MATERIALS: Monolayers of human fibroblasts. INTERVENTION(S): Exposure of human fibroblast monolayers to several concentrations of morphine, for different periods of time, with and without an artificially induced inflammatory process. MAIN OUTCOME MEASURES: Cell count, cell viability, cell proliferation and apoptosis. RESULTS: A concentration, time and exposure-dependent cytotoxic effect of morphine-mediated apoptosis was observed. Simulated inflammatory conditions seemed to lessen toxic effects. CONCLUSION: Cytotoxic effects of morphine are exposure, time and concentration dependent. Simulating aspects of inflammatory conditions seems to increase resistance to morphine cytotoxicity especially in the presence of higher concentration and longer exposure times.